Messenger of Allah (peace and blessings of Allah be upon him): Islamic Communication Ethics Study Hadith Perspective - Hijrayanti Sari; St. Maghfirah Nazir (International Journal of Islamic Studies Issues, 2025)
This study is a library research with a qualitative descriptive approach. The purpose of this study is to examine the exemplary behavior of the Prophet and the method of advising that he applied in instilling Islamic values. Including also how the implications of the hadiths are for the development of Islamic communication in the modern era. The results of the study are that the Prophet used exemplary behavior to teach the practice of worship and morals. In advising he used 6 methods, namely touching the heart, discussion, parables, logical satisfaction and paying attention to time. These hadiths then became an ethical framework in the development of Islamic communication.